1963
DOI: 10.1119/1.1969140
|View full text |Cite
|
Sign up to set email alerts
|

Maxwell, Displacement Current, and Symmetry

Abstract: Maxwell's reasons for introducing displacment current are considered. His published works disclose no arguments based upon symmetry, but emphasis on the symmetry of Maxwell's equations with regard to electric and magnetic fields is found in Oliver Heaviside's work on electromagnetic theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…A review of some of the secondary literature [36,37,38,39,40,41,42] found no mention of charge conserving alternatives to Maxwell's displacement current, though it is reported that some of Maxwell's distinguished contemporaries simply did not accept it. Further, in gracious replies to this writer's queries, Prof. J.Z.…”
Section: History Of Some Related Mattersmentioning
confidence: 99%
“…A review of some of the secondary literature [36,37,38,39,40,41,42] found no mention of charge conserving alternatives to Maxwell's displacement current, though it is reported that some of Maxwell's distinguished contemporaries simply did not accept it. Further, in gracious replies to this writer's queries, Prof. J.Z.…”
Section: History Of Some Related Mattersmentioning
confidence: 99%
“…Otros plantean alguna alternativa para desarrollar el tema en el aula (Terry, 1981), y otros estudian el desarrollo histórico del concepto (Bork, 1963;Siegel, 1991). La revisión bibliográfica llevada a cabo muestra una escasez de artículos que analicen en profundidad los problemas de aprendizaje relacionados con este tema.…”
Section: Marco Teórico Y Problema De La In-vestigaciónunclassified
“…[15][16][17] However, in these, the model corresponds to well defined D and H, in-effect also demanding they are measureable, when in fact this is not necessary. [18][19][20][21][22][23][24] To avoid this unnecessary assumption, an alternative approach based purely on the physically measurable fields E and B was developed, [12] and this is what we use here.…”
Section: Introductionmentioning
confidence: 99%